Acanthamoeba produces disseminated infection in locusts and traverses the locust blood-brain barrier to invade the central nervous system - Kirk Ruth; Goldsworthy Graham; Mortazavi Parisa N; Khan Naveed A (BMC Microbiology, 2010)
Abstract Background Many aspects of Acanthamoeba granulomatous encephalitis remain poorly understood, including host susceptibility and chronic colonization which represent important features of the spectrum of host-pathogen interactions. Previous studies have suggested locusts as a tractable model in which to study Acanthamoeba pathogenesis. Here we determined the mode of parasite invasion of the central nervous system (CNS). Results Using Acanthamoeba isolates belonging to the T1 and T4 genotypes, the findings revealed that amoebae induced sickness behaviour in locusts, as evidenced by reduced faecal output and weight loss and, eventually, leading to 100% mortality. Significant degenerative changes of various tissues were observed by histological sectioning. Both isolates produced disseminated infection, with viable amoebae being recovered from various tissues. Histological examination of the CNS showed that Acanthamoeba invaded the locust CNS, and this is associated with disruption of the perineurium cell/glial cell complex, which constitutes the locust blood-brain barrier. Conclusions This is the first study to demonstrate that Acanthamoeba invades locust brain by modulating the integrity of the insect's blood-brain barrier, a finding that is consistent with the human infection. These observations support the idea that locusts provide a tractable model to study Acanthamoeba encephalitis in vivo. In this way the locust model may generate potentially useful leads that can be tested subsequently in mammalian systems, thus replacing the use of vertebrates at an early stage, and reducing the numbers of mammals required overall.